Container – Terminal – Gate – System Optimization - Mazouz, Abdelkader; Naji, Loay; Lyu, Yuanzhi (Journal of Applied Business Research, 2017)
The utility of the container terminal has become quite remarkable all over the world. It is vital to maximize the utility of the container yard and the terminal gate system. With the ever-increasing importance of containerization in the world, more than 60% of cargo is transported by containers, this ratio even reaches 100% in some highly economic developed and political stable places. It is estimated that, the total quantity of containerization in the world will increase by 10% every year before 2020. The aim of this work is to be used as a decision support system tool when designing and constructing container terminals. The article focuses on optimizing the staging of containers within a terminal gate system. A Port within the main Land China is being used as a test bed to demonstrate the Simulation Model based on Queuing Theory. The analysis considers both the facility and the setting of the terminal gate system by considering the Discrete Event System Theory and the terminal gate system in order to make the daily operation more suitable for the terminal. The research combines the computer simulation method and the actual complex discrete event system, and identifies the most suitable setting and the theoretical maximum capacity for the terminal. Normally, the usage ratio (the busy time) should be around 75%, the simulation findings, the channel performance measures indicators are the usage ratio and the average waiting time the proper number of channel is 3 for entrance channel, and 2 for exit channel with usage ratios of 74% and exit usage of 55%, allocating 3 Entrance Channel (gates) and 2 Exit Channels (gates). Both the entrance and exit saved 2 channels. Both the capacity and channel number calculation are treated as a reference for the future decision maker when it comes to the container terminal construction.